ANALISIS IMPLEMENTASI KEBIJAKAN PERIMBANGAN KEUANGAN ANTARA PEMERINTAH PUSAT DAN PEMERINTAH DAERAH DALAM ERA OTONOMI DAERAH DI KOTA PALU - Putriani, Dhian (Katalogis, 2013)
This research aimed at finding out the implementation of finance balance policy between central government and regional government in regional autonomy era in Palu City. This was descriptive research with the type of field research. Data sources or informants were SKPD leader or finance sub unit leaders in Regional Secretariat of Palu City, the head of Regional Development Palnning Board, and the head of Regional Income Official of Palu City. Data sources of this research consisted of primary and secondary data that were collected through observation, interview, and documentation. The data were analyzed by using qualitative analysis, organizing data andinformation basedon facts obtaimed in the field, and by adoptingdescriptiveanalysis, getting the detail description of research object through the steps: data editing, data category, data interpretation, and formulating conclusion of this research. The result showed that the implementation of finance balance policy between central government and regional government in regional autonomy era in Palu City had been running well based on the criteria: communication, resources, disposition/character, and bureaucracy hierarchy.